Comprehensive HPV genotyping in Fars, Iran: Molecular epidemiology and implications for prevention - Amirreza Radfar; Neda Pirbonyeh; Afagh Moattari (Journal of Clinical Virology Plus)
Background: Human papillomavirus (HPV) is the most prevalent sexually transmitted infection, with high-risk genotypes contributing to cervical and other cancers. While HPV epidemiology has been studied in Iran, comprehensive genotype distribution data remain limited for Fars province. This study examines HPV prevalence and genotype distribution to inform regional prevention strategies. Methods: This cross-sectional study analyzed 616 samples collected from a clinical laboratory between 2021 and 2024. HPV DNA was detected using nested PCR, and genotyping was performed via reverse hybridization. Associations between HPV status, risk classification, gender, and sample collection method were statistically assessed. Results: Overall, 56.3 % of individuals tested positive for HPV. High-risk HPV was detected in 56.6 % of positive cases, with HPV-16 (29.6 %) and HPV-18 (6.8 %) being the most common oncogenic types. Low-risk HPV-6 (35.0 %) and HPV-11 (17.1 %) were also prevalent. No significant associations were found between HPV status and age (p = 0.346), gender (p = 0.998), or sample collection method (p = 0.998). Conclusion: The predominance of vaccine-covered HPV types underscores the need for expanded screening and targeted prevention programs in Fars province. Although demographic factors were not significantly associated with HPV status, the high burden of high-risk types necessitates stronger regional public health interventions. These findings contribute valuable epidemiological data to enhance HPV control measures and optimize vaccination policies.